Cinderella in the billionaire's castle - Connelly, Clare (Harlequin presents, 2022)
"Tormented by the guilt of his past, Thirio Skartos hides in the shadows of his Alpine castle. He's deprived himself of the wild pleasures he used to crave. Until Lucinda Villeneuve makes it beyond his imposing steel-reinforced door. Wedding planner Lucinda must persuade the superrich recluse to hire her. It's the only way to reclaim her rightful place in her father's company. But when a storm leaves her stranded, she has no choice but to stay... And to resist a totally forbidden night in Thirio's powerful arms!" -- Page [4] cover.